(untitled) (Latakia University Journal -Basic Sciences Series, 2016)
تمَ من خلال هذا البحث حل المعادلة الحركية شبه الكلاسيكية في بلازما فيرمي الكمية، وتعد هذه المعادلة تعميماً لمعادلة لانداو الحركية؛ حيث تتضمن معلماً فيزيائياً إضافياً يسمى حد مادلونغ ناتج عن انعراج أمواج دو-بروي، وهذا الحد مسؤول عن إثارة الصوت الصفري في غاز فيرمي المثالي. كذلك عممنا عبارة تبدد الصوت الصفري لـِ لانداو بوجود التصحيح الكمي. ولتحقيق ذلك قمنا بنشر تابع التأثير المتبادل بين أشباه الجسيمات وفق التوافقيات الكروية في فراغ ثلاثي الأبعاد من أجل( =0 ,1). تسمى عوامل نشر هذا التابع (بارامترات لانداو)، بعد ذلك أوجدنا عبارة تبدد الصوت الصفري وقمنا بمقارنتها مع ماتوصل إليه آخرون في هذا المجال. In this paper, quantum kinetic equation in Quantum Fermi Plasmas have been solved, which is considered a generalization of Landau Kinetic Equation. There is an additional physical feature included here; namely, the Madelung term is produced due to the diffraction of de-Broglie waves. This term is responsible for the excitation of zero sound even in an ideal Fermi gas. Thus, we have generalized Landau dispersion of zero sound including the quantum correction. To achieve that, we had expanded interaction function between quasi- particles by means of spherical functions in three-dimension space for ( =0,1), these parameters are called (Landau parameters). After that, the dispersion relation of zero sound have been found and compared with other studies in the same domain.